2001
DOI: 10.5194/nhess-1-15-2001
|View full text |Cite
|
Sign up to set email alerts
|

Morphotectonic properties of the Lo River Fault near Tam Dao in North Vietnam

Abstract: Abstract. The Lo River fault near Tam Dao, North Vietnam, is a young, right-lateral, normal fault which has been active throughout the Quaternary. Rates of dextral slip range between 1 and 2 mm/yr whereas rates of uplift can be estimated roughly at 0.1-1 mm/yr. The drainage deflection and arrangement of shutter ridges suggest 1.5-2.0 km of dextral offset during the past 1-2 millions of years (m. y.), and the height of the youngest faceted spurs averages at 170 m. Analysis of morphometric parametres of the moun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(47 citation statements)
references
References 6 publications
0
43
0
4
Order By: Relevance
“…In the aspect of tectonics, the Hoanh Bo Basin is situated in the eastern part of the Red River Fault Zone, where the Day Nui Con Voi Massif is present, and it has key significance for understanding of the Paleogene-Neogene geodynamic evolution of the southeast Asia (Cuong & Zuchiewicz 2001, Cuong 2007.…”
Section: Introductionmentioning
confidence: 99%
“…In the aspect of tectonics, the Hoanh Bo Basin is situated in the eastern part of the Red River Fault Zone, where the Day Nui Con Voi Massif is present, and it has key significance for understanding of the Paleogene-Neogene geodynamic evolution of the southeast Asia (Cuong & Zuchiewicz 2001, Cuong 2007.…”
Section: Introductionmentioning
confidence: 99%
“…1(a)). A number of other obvious fault zones have been reported in this region, such as the Cao Bang-Tien Yen (Cuong et al, 2006), Dong Trieu (Charusiri et al, 2002), Song Ca (Takemoto et al, 2005), Song Chay (Cuong and Zuchiewicz, 2001), and Song Da and Song Ma (Phoung, 1991) fault zones (nos. 1, 5, 40, 41, 42, and 43 in Fig.…”
Section: Active Fault Datamentioning
confidence: 99%
“…The V f index has seldom been applied to active tectonic areas in the tropics. A V f analysis along the Lo River Fault in northern Vietnam produced low values (0.06 to 0.61), indicating recent uplift upon the fault (Cuong and Zuchiewicz, 2001).…”
Section: Ratio Of Valley Floor Width To Valley Height (Vf )mentioning
confidence: 99%
“…Morley et al (2007) and Fenton et al (2003) suggested that the fault is characterized mainly by normal dip-slip and subordinate left-lateral slip. (Cuong and Zuchiewicz, 2001).…”
Section: Sense Of Fault Movementmentioning
confidence: 99%
See 1 more Smart Citation